KEKUASAAN AGAMA PADA MASA ABAD KEGELAPAN DI PRANCIS DALAM NOVEL NOTRE-DAME DE PARIS KARYA VICTOR HUGO (ANALISIS SOSIOLOGI SASTRA) - , AYU ANINDITA DWI LESTARI, Drs. Ali Shahab ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Middle Ages was a long period of European history, including France. This century is also known as the Dark Ages, it is due to the absolute religious power of the the Church. These conditions led in to a number of distortions and dark historical events, such as retardation of science, the emergence of myth and superstition, inquisition, et cetera. Those social occurences in the Middle Ages are found in the novel Notre-Dame de Paris by Victor Hugo. Therefore, this study focuses on the distortion of religious power in the Middle Ages by applying the literary sociological analysis from Alan Swingewood. Furthermore, various issues regarding to the effect of distortion religious power contained in the novel are analyzed by utilizing the theory of power by Lord Acton and the theory of theocracy by St.Agustinus. Based on this research, the distortion that emerged in the Middle Ages is caused by the use of infinite power. The analysis also presents the several kinds of criticism and the technique of author in criticizing.